Works councils and absenteeism of apprentices : an empirical analysis - Pfeifer, Harald [Verfasser] (My University, 2020)
"This article examines the influence of works councils on apprentices' absence from the workplace in Germany. The analysis draws on merged administrative and survey data that include information about the cumulated days that apprentices are absent from work due to sickness. Regression results imply that the existence of a works council in a firm significantly reduces apprentices' absence. However, split-sample regressions show that this is predominantly the case in firms with high absence rates. Overall, the results suggest that works councils exercise their legally anchored 'voice' function in the German apprenticeship system." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.5.4 Sozialpartner; Betriebliche Berufsausbildung; Auszubildender; Fehlzeiten; Einflussfaktor; Betriebsrat; Regressionsanalyse